Highly enhanced durability of a graphitic carbon layer decorated PtNi3 alloy electrocatalyst toward the oxygen reduction reaction. Issue 40 (26th April 2019) - Sun, Kui; Li, Jia; Wang, Feng; He, Wenxiang; Fei, Minfei; Lu, Zhenda; Zhang, Huigang; Liu, Jianguo; Zou, Zhigang
Abstract : An N-doped graphitic carbon layer was for the first time introduced to greatly enhance the durability of a PtNi3 /C alloy catalyst in an acidic environment. Abstract : The durability issue of a carbon supported PtNi3 alloy catalyst (PtNi3 /C) under acidic conditions has been solved by introducing an N-doped graphitic carbon (NGC) layer to coat the surface of the PtNi3 /C catalyst. The as-prepared PtNi3 /C@NGC catalyst exhibits superior durability, being able to undergo 10 000 voltage cycles with negligible activity decay.